Sildenafil in the prevention of hepatic ischemia/reperfusion injury in rats - Leão, Layra Ribeiro Souza; Lima, Hilkéa Carla Souza Medeiros; Rêgo, Amália Cínthia Meneses; Azevedo, Ítalo Medeiros; Dantas-Filho, Antonio Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2010)
Purpose: This study aimed to determine the effect of sildenafil on the liver, when administered prior to the episode of liver ischemia/reperfusion. Method: We used 12 Wistar rats. In both IR group (n=6) and IR sildenafil group (n=6), hepatic ischemia was induced for 45 minutes by occlusion of blood vessels supplying the median and lateral lobes of the liver using a vascular clip (bulldog). IR group animals were treated with sildenafil citrate at a dose of 0.7 mg/kg by gavage, 30 minutes before ischemia. During the observation period of ischemia/reperfusion, the abdomen was temporarily closed. After 45 min the vascular clamp was removed, and reperfusion occurred by 60 min. Liver biodistribution of Tc-99m-phytate, histopathology and serum AST, ALT, LDH were analyzed. Results: In animals treated with sildenafil the right lobe of the liver (without ischemia) had significantly higher radioactivity uptake than in the untreated rats (p <0.001). After ischemia/reperfusion, sildenafil failed to improve the radioactive uptake in the left lobe (p = 0.01). Comparing the right and left lobes, the radioactive uptake was lower in lobe left than in right lobe (p = 0.005) of untreated rats (controls). The liver function tests were significantly more impaired in the group treated with sildenafil than in controls. Conclusion: Sildenafil contributed to the deterioration of liver function in a model of ischemia/reperfusion.